The Role of Electronic Service Quality in Establishing Customer Satisfaction and Trust in E-Commerce Platforms - WK, WAHYU NURJAYA; Nuralisa, Mike; Ramadhona, Marini; Firdaus, Adam; Sugiana, Neng Susi Susilawati (Jurnal Teknologi Informasi, 2025)
The rapid evolution of e-commerce platforms has elevated the significance of electronic service quality (e-service quality) in shaping customer satisfaction and trust. This study aims to examine how e-service quality dimensions—such as reliability, responsiveness, assurance, and website usability—affect customer satisfaction and trust across different cultural backgrounds. A cross-cultural quantitative research design was employed to gather insights from 100 respondents representing diverse nationalities who actively engage in online shopping. Data were collected through structured questionnaires and analyzed using SPSS software to determine the relationships among variables. The findings reveal that e-service quality has a significant and positive impact on both customer satisfaction and trust. Among the service dimensions, website usability and responsiveness emerged as the most influential factors across cultures. Furthermore, the results highlight variations in customer perceptions based on cultural context, suggesting that e-commerce platforms must tailor their service strategies to accommodate cultural preferences. From a practical standpoint, these insights provide actionable implications for e-commerce businesses seeking to enhance their competitive edge in a global market. By understanding the cultural nuances that shape customer expectations, online platforms can develop more personalized and effective service strategies to boost customer loyalty. The uniqueness of this study lies in its cross-cultural approach, combining service quality analysis with cultural sensitivity to deliver more inclusive e-commerce insights. This perspective addresses a critical gap in prior research, which often overlooks cultural influences in service quality assessment.